DSS Using MABAC,MOORA For Selection of Majors According to Students' Interests - Sari, Ayulita Purnama; Oktavia, Tanty (Sinkron : jurnal dan penelitian teknik informatika, 2023)
In the current digital era, individual abilities are needed to be more creative and innovative in various fields, so that vocational students must better prepare their competencies. In this case the competence is related to the major they choose. On average, students take the wrong major about 35%, follow friends around 50%, for students who really choose the right major 15%. For this, the MABAC and MOORA decision support system methods are needed in terms of determining majors according to student interests and talents. System development uses the Waterfall method. The purpose of this study is to design a decision support system that can be used for selecting majors according to student interests by utilizing the results of a comparison of the MABAC and MOORA methods. The results of this study illustrate the MOORA calculation for major selection, so prospective students get the decision to choose the Multimedia major because it has the highest score. From the MABAC calculations for the selection of majors, prospective students get the decision to choose the Accounting major because it has the highest score. The comparison of the mabac and moora methods is where mabac has the highest decision outcome value compared to the decision outcome value of the moora method so that the mabac method is used to assist decision making in selecting majors according to interests.